HUBUNGAN POWER OTOT TUNGKAI DENGAN KEMAMPUAN TENDANGAN LURUS ATLET PENCAK SILAT STARLAK KUINTAL STROPEDO DANAU BINGKUANG - Esiska Yanirma; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: based on the background that created and with the phenomena exists, then the research can be formulated as follows: If there is a power relationship of limb muscles with the ability to kick straight STARLAK pencak silat athletes KUINTAL STROPEDO (SKS) Lake Bingkuang, in accordance with the issues raised above, the purpose of this research is to know the power relationship with limb muscles ability kicks straight athletes pencak silat STARLAK KUINTAL STROPEDO (SKS) Lake Bingkuang. Data that has been collected and then analyzed. That becomes the variable X is power and limb muscles that become variable Y is the ability to kick straight. As for the hypothesis to be tested, "there is a power relationship of limb muscles with the ability to kick straight Athletes Pencak Silat Starlak Kuintal Stropedo". The results of calculations can be known that great value for the correlation of power limb muscles against a straight kick ability athletes pencak silat starlak kuintal stropedo is 0.95. After a number of correlation obtained, further hypothesis testing is done if there is a power relationship of limb muscles against a straight kick ability athletes pencak silat starlak kuintal stropedo where rhitung found = 0.95. On a significant level of 5% was found to be rtabel = 0.444. Thus rhitung > rtabel or 0.95 > 0.444. This indicates the existence of a correlation between variables X and Y variables or there is a significant relationship of power limb muscles against a straight kick ability athletes pencak silat starlak kuintal stropedo.Key Words : Power Limb Muscles, The Ability The Kick Straight Athletes Pencak Silat Starlak Kuintal Stropedo